Analysis of Ship Manning in the Crewing Department in Preventing Crew on Board Delays at PT. Pelayaran Andalas Bahtera Baruna Jakarta - Yasin, Fauzi Alwi; Setiono, Beni Agus; Purwiyanto, Didik (Universitas Hang Tuah, 2025)
The crew is the main element in running the ship's operations. It is important to procure or dispatch crew members. However, crew dispatch has a relatively long and drawn-out process and often crew members do not follow the process according to schedule, causing delays. This research is a qualitative study that aims to determine the causes of crew on board delays. Data collection in this study used interviews, observation, and documentation methods. The results of this study indicate that there are obstacles in the ship's crew process. From the results of data analysis, the causes of crew on board delays are due to several factors, namely delays in certificate revalidation, difficulty in finding candidates according to qualifications, and sudden changes in crew requests. Efforts that can be made in overcoming this delay problem include giving a statement letter and sanctions if you do not follow existing procedures.